2011
DOI: 10.1371/journal.pone.0019418
|View full text |Cite
|
Sign up to set email alerts
|

New Noncovalent Inhibitors of Penicillin-Binding Proteins from Penicillin-Resistant Bacteria

Abstract: BackgroundPenicillin-binding proteins (PBPs) are well known and validated targets for antibacterial therapy. The most important clinically used inhibitors of PBPs β-lactams inhibit transpeptidase activity of PBPs by forming a covalent penicilloyl-enzyme complex that blocks the normal transpeptidation reaction; this finally results in bacterial death. In some resistant bacteria the resistance is acquired by active-site distortion of PBPs, which lowers their acylation efficiency for β-lactams. To address this pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…Docking was performed on the X-ray crystallography structure of PBP2a (PDB: 4CJN) and the 11,421 ligands from the Zinc In Man database, 42 plus eight experimentally approved PBP2a inhibitors with IC 50 less than 100 mM. 43 These eight approved inhibitors served as the ''true'' hits in this validation. Added together, a ligand library of 11,429 was formed.…”
Section: Evaluation Of Docking Methodsmentioning
confidence: 99%
“…Docking was performed on the X-ray crystallography structure of PBP2a (PDB: 4CJN) and the 11,421 ligands from the Zinc In Man database, 42 plus eight experimentally approved PBP2a inhibitors with IC 50 less than 100 mM. 43 These eight approved inhibitors served as the ''true'' hits in this validation. Added together, a ligand library of 11,429 was formed.…”
Section: Evaluation Of Docking Methodsmentioning
confidence: 99%
“…10,11 Others strategies to treat MRSA have centered on the development of new drug classes with orthogonal mechanisms to the β-lactams such as linezolid, daptomycin, and new glycopeptides. 12 Nevertheless resistance to these novel classes has already been reported.…”
mentioning
confidence: 99%
“…A number of non‐β‐lactam compounds have been reported that bind to and, in some cases, inhibit certain PBPs. These include derivatives of rhodanines, 119 boronates, 120–122 several dyes, 123 4‐quinolones, 124 and some substituted benzoic acids 34 . Of these, only the boronates are thought to be covalent, albeit reversible, inhibitors.…”
Section: Extracytoplasmic Targetsmentioning
confidence: 99%
“…These include derivatives of rhodanines, 119 boronates, 120-122 several dyes, 123 4-quinolones, 124 and some substituted benzoic acids. 34 Of these, only the boronates are thought to be covalent, albeit reversible, inhibitors. Any antibacterial activity associated with these non-␤lactam compounds has not been causally linked to PBP binding.…”
Section: Extracytoplasmic Targetsmentioning
confidence: 99%